2014
DOI: 10.1177/0363546514526151
|View full text |Cite
|
Sign up to set email alerts
|

Head Trauma in Mixed Martial Arts

Abstract: Rates of KOs and TKOs in MMA are higher than previously reported rates in other combative and contact sports. Public health authorities and physicians should be cognizant of the rates and mechanisms of head trauma. Preventive measures to lessen the risks of head trauma for those who elect to participate in MMA are described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
90
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(94 citation statements)
references
References 17 publications
1
90
1
2
Order By: Relevance
“…36 Video analysis reported that the rate of match-ending head trauma was 15.9 per 100 athletic exposures (31.9% of matches). 41 All knockouts were attributable to direct head trauma, with 53.9% being strikes to the mandibular region. In the 30 seconds before match stoppage, losers sustained an average of 18.5 strikes, with 92.3% of them to the head.…”
Section: Injury Riskmentioning
confidence: 99%
“…36 Video analysis reported that the rate of match-ending head trauma was 15.9 per 100 athletic exposures (31.9% of matches). 41 All knockouts were attributable to direct head trauma, with 53.9% being strikes to the mandibular region. In the 30 seconds before match stoppage, losers sustained an average of 18.5 strikes, with 92.3% of them to the head.…”
Section: Injury Riskmentioning
confidence: 99%
“…A recent article in The American Journal of Sports Medicine entitled ''Head Trauma in Mixed Martial Arts,'' written by Michael G. Hutchison, David W. Lawrence, Michael D. Cusimano, and Tom A. Schweizer, 5 is about a critically important topic that deserves our undivided attention. Mixed martial arts (MMA) shows a recent increase in popularity and is a full combative sport with a high rate of injuries, particularly head injuries.…”
Section: Head Trauma In Mixed Martialmentioning
confidence: 99%
“…The American Medical Association (AMA) describes MMA as ''violent and dangerous'' and expresses its concerns about the aggressiveness of the sport and it causing physical harm, specifically brain injuries. 5 A comparison was made between match scorecards and digital video recordings of matches. Conclusions showed that rates of head injuries in MMA are higher than those reported in boxing.…”
Section: Head Trauma In Mixed Martialmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Without detailed information about the athletes' neurocognitive status or pattern of recovery, conclusions about concussion rates have generally relied on inference, 5 the recorded assessment of the ringside physician, 3,6,11,15 or the recollections of individual fighters. 13 In this issue of the American Journal of Sports Medicine, Hutchison and colleagues 8 report the results of their extensive analysis of head trauma in professional MMA. This is a timely study, since a recent article has reported diffusion tensor imaging abnormalities suggestive of microscopic brain damage in boxers and MMA fighters.…”
mentioning
confidence: 99%